Quercetin activates vitamin D receptor and ameliorates breast cancer induced hepatic inflammation and fibrosis - Sannappa Gowda, Nirmala G.; Shiragannavar, Varsha D.; Puttahanumantharayappa, Lakshana D.; Shivakumar, Ashwini Tumkur; Dallavalasa, Siva; Basavaraju, Chaithanya G.; Bhat, Smitha S.; Prasad, Shashanka K.; Vamadevaiah, Ravishankar M.; Madhunapantula, SubbaRao V.; Santhekadur, Prasanna K. (Frontiers in Nutrition, 2023)
Aims To explore the hepatoprotective role of quercetin and its novel molecular mechanism of action on breast cancer associated hepatic inflammation and fibrosis via Vitamin D receptor (VDR). Main methods We used Ehrlich Ascites Carcinoma (mouse mammary carcinoma) model for our in-vivo experiments and human breast cancer cell lines for in-vitro assays. We inoculated 1.5 × 106 Ehrlich ascites carcinoma cells into female Swiss albino mice. Quercetin (50 mg/kg) was administered intraperitoneally for 15 days. Liver enzymes activity was determined using a spectrophotometric assay. The hallmarks of inflammation and fibrosis were determined using Immunohistochemistry. The effect of quercetin on tumor formation was elucidated using human breast cancer cell lines and chick chorioallantoic membrane assay. Docking study was performed to explore the binding mode of quercetin with VDR. Key findings In EAC tumor-bearing mice, cell numbers, tumor volume, body weight and liver weight were dramatically increased, while they significantly decreased in mice treated with quercetin. Additionally, the peritoneal neo-angiogenesis was also significantly suppressed in the quercetin-treated mice, compared to the control. In addition, quercetin treated EAC tumor bearing mice had lower levels of liver enzymes, decreased hepatic inflammation and fibrosis compared with EAC tumor bearing mice. Docking study confirmed VDR-quercetin interaction. Furthermore, in-vitro assays and chick chorioallantoic membrane assay revealed the Vitamin D mimicking effect of quercetin. Significance Dietary flavonoid, quercetin could act as a promising therapeutic drug to suppress the breast cancer induced tumor angiogenesis, hepatic inflammation, and fibrosis possibly via activation of VDR.